TRANSMISSIBILITY OF H9 SUBTYPE OF AVIAN INFLUENZA VIRUS IN VACCINATED AND NON-VACCINATED BROILER CHICKEN EXPOSED TO EXPERIMENTALLY CHALLENGED BIRDS - Qurat ul Ain; Arfan Ahmad; Aftab Ahmad Anjum; Mamoona Chaudhry (Journal of Animal and Plant Sciences, 2023)
This study aimed to evaluate the efficacy of various avian influenza virus subtype H9 vaccines for their potential to stop or reduce the virus shedding and transmission in broiler birds exposed to challenge birds. At 6th day of age 3 groups of birds (A, B, C) comprising 10 birds each were vaccinated with imported (Ivac), local (Lvac) and self -prepared (Spvac) vaccines while groups D, E and F were kept as non-vaccinated control groups. On 25th day of age, birds of group D were challenged through intranasal route with 100 EID50 of H9 virus and housed with vaccinated birds of groups A, B, C and non- vaccinated group E. Group F was kept in isolation in a separated shed. All the experimental birds were observed twice a day for any clinical signs of AI for 10 days and cloacal swabs were collected on daily basis, post exposure to evaluate the number of shedders and viral load quantification by real time RT-PCR. In directly challenged group D, virus shedding started one day earlier (2nd Day Post Challenge -DPC) than other groups (3rd Day Post Exposure-DPE). On 2 DPC, 50 % birds showed virus shedding with 3037.5copies/µL of viral load. In vaccines groups, 30-40 % shedders were identified with viral load ranging from 432.45 copies/µL on 3rd DPE. The number of virus shedders increased and reached maximum on 6th DPC (100%) with viral load 59427921.8 copies/µL copies in group D whereas the maximum shedders were evidenced on 6th DPE in all the vaccinated groups (50-60%) with viral load ranging from 2235.7copies/µL. The virus shedders and load were decreased in all the vaccine groups on 6th DPE. The virus shedding stopped on 9th DPE in local vaccinated group B than imported and self-prepared vaccinated groups (10th DPE) however in group D virus shedding didn’t stop till the end of experimental trial. In group E, the number of shedders and viral load was less than group D but more than all the vaccinated groups throughout the experiment trail. None of the birds in group F showed virus shedding. Statistically all vaccines proved effective to reduce virus shedding and transmission than directly challenged group D and E (p<0.05) and may be used to combat AIV H9 infection. Based on this study it may be concluded evaluation of viral shedding is critical for determining the efficacy of avian influenza (H9) vaccines in broiler chickens
Keywords: Transmissibility; AIV-H9; Vaccination; Self-prepared Vaccine; Viral load Quantification